2017
DOI: 10.3390/su9091614
|View full text |Cite
|
Sign up to set email alerts
|

Demand-Oriented Design Strategies for Low Environmental Impact Housing in the Tropics

Abstract: This study aims to propose design strategies for low environmental impact (low-EI) housing in the tropics while incorporating user needs to increase its acceptance in the market. The Fuzzy Delphi method (FDM) is adopted initially to draw the user needs for contemporary housing, after which the crucial design factors are identified. The analytic network process (ANP) and house of quality (HOQ) are further utilized to incorporate weightings of user needs into crucial design factors to establish appropriate desig… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
5
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 7 publications
(5 citation statements)
references
References 57 publications
0
5
0
Order By: Relevance
“…To establish the standard ELM model, first of all, we need to program in MATLAB2018a platform to get the ELM algorithm program [24]. e best performance of the Sigmoid was found through simulation analysis of the excitation function in the same number of hidden layers and regularization [8].…”
Section: Elm Modelmentioning
confidence: 99%
“…To establish the standard ELM model, first of all, we need to program in MATLAB2018a platform to get the ELM algorithm program [24]. e best performance of the Sigmoid was found through simulation analysis of the excitation function in the same number of hidden layers and regularization [8].…”
Section: Elm Modelmentioning
confidence: 99%
“…Studies have shown that implementation of bioclimatic strategies in design and construction of residential buildings is correlated with the resident's satisfaction [38,67,69] as well as minimises energy consumption and improves indoor thermal environment of buildings [19,[70][71][72][73][74]. Another study [32] has also found that utility, durability and comfort are the three greatest user needs for building. Different bioclimatic practices have been found from the literature as having potentials of improving indoor environmental conditions and minimising energy consumption of residential buildings.…”
Section: Literature Reviewmentioning
confidence: 99%
“…However, people's environmental comfort in a building depends on adaptation with climatic factors such as wind, and sun [22]. Similarly, Zhang et al [32] stated that the shape, internal spatial arrangement, size of a building and the azimuth of the sun all affect the energy consumption of a building. Regrettably, application of bioclimatic concept in the design and construction of building has not shown any significant results in building operation [21], due to lack of understanding [33].…”
Section: Introductionmentioning
confidence: 99%
“…Delbecq Zhang et al found that the market acceptance of low-impact housing-design strategies in the tropics was enhanced when key design factors were identified in combination with user needs using FDM. However, the number of samples and the selection of experts are important factors influencing the FDM results, which rely on the achievement of these experts' consensus on the issue at hand [15]. Dalkey and Helmer recommended panels of between 10 and 30 experts to minimize error values and obtain the highest experimental reliability [16].…”
Section: Research Processmentioning
confidence: 99%